The development of active element "Lecture" in the control system of MOODLE studying for computer disciplines - Litvinov, A. (Problems of Engineer-Pedagogical Education, 2018)
The results of the elaboration of the active element “Lecture” in the Moodle learning management system for computer science in relation to distance education are presented at the article. The analysis of of system Moodle use in education is carried out. Is says that the most part of publications has described character, frequently repeating technical manuals of a site of users Moodle and seldom takes into account features of concrete fields of knowledge. The generalized flow diagram of a lecture for computer disciplines is formulated and for it the flow diagram for the lecture “Processors of Computer Systems” is designed from the Moodle pages. It contains a general purpose of the computer processor and its components as well as control questions after each section. The lecture is realized in electronic form, it is an integral part of the distance learning course “Architecture of computer systems”. It is possible to use lecture «Processors of Computer Systems» as example in the development of lectures on other themes. Thus time for their development and debugging is significantly reduced. Approbation of lecture was carried out on full-time students. It was intensively used by them in preparing for the exam and proved to be useful, especially for those students who have missed the corresponding lecture.